Potential of Chromolaena odorata Leaf as A Cure of Aeromonas hydrophila on Giant Gouramy (Osphronemus gouramy) - Y. Hadiroseyani; . Hafifuddin; M. Alifuddin; H. Supriyadi (Jurnal Akuakultur Indonesia)
This study was conducted to examine the potency of Chromolaena odorata leaf extract as a medicine for skin eruption disease caused by  Aeromonas hydrophila in giant gouramy Osphronemus gouramy.  Leaf extract of Chromolaena odorata for in vitro test was 0 (as control), 13000, 15000, 17000, 19000 and 21000 ppm, poured onto TSA medium containing bacteria 103 cfu/ml, and then is incubated for 24 hours. In vivo test was performed by injecting bacteria 0.1 ml of 109 cfu/ml intramuscularly into giant gouramy (14 g weight), and then  fish were maintained in the water containing 15000 ppm of Chromolaena odorata leaf extract. In vitro study showed that prevention area of leaf extract against Aeromonas hydrophila was increase by increasing the concentration of leaf extract used, reached 9,33 mm.  Prevention zone of leaf extract by difusion tends to constant, reached 7,6 mm. By in vivo test, survival rate of giant gouramy infected by Aeromonas hydrophila was no significantly different between dosages of leaf extract.  All treated fish, excluded control died after 24 hours infection.